Similarities and differences in the formation and use of interjective phraseological units Russian and Kabardian-Cherkassian languages - Angela A., Afaunova (Kavkazologiya, 2024)
The article presents the results of the analysis of interjectional phraseological units of the Russian and Kabardino-Circassian languages in a comparative aspect. The purpose of the article is to study, typologize interjectional phraseological units of the Kabardian-Circassian language and compare them with the Russian language (determining what is common and what is different in semantics, in methods of formation and use). This work provides a review of the works of leading linguists who analyzed phraseological units both in the Adyghe languages and in domestic linguis-tics, and selected and studied extensive illustrative material on the languages under study. When preparing the article, such methods of linguistic research as description, comparison, juxtaposi-tion, method of scientific and grammatical analysis, classification and typologization were used. The work proves that in the functional sphere of interjection phraseological units, the same features that characterize other types of phraseological units and interjection words find their place, i.e., determine national and cultural specifics, reflect well-known historical events; show emotionality; in terms of semantic meaning, they fully correspond to the expressions; do not act as members of the proposal. It has been established that most interjection phraseological units form synonymous series under the requirements placed on them, like independent words. The study proposes the author’s classification of the analyzed units according to the method of formation, according to the activity of use, and according to composition.